Phloem loading by the PmSUC2 sucrose carrier from Plantago major occurs into companion cells - Stadler, Ruth; Brandner, Johanna; Schulz, Alexander; Gahrtz, Manfred; Sauer, Norbert (The Plant Cell, 1995)
High levels of mRNA for the sucrose-H symporter PmSUC2 have been found in the vascular bundles of petioles from Plantago major. The possible role of PmSUC2 in phloem loading was studied with antiserum raised against the recombinant PmSUC2 protein. This antiserum labeled a single 35-kD protein band in detergent extracts of P. major vascular bundles. It showed no cross-reaction with the P. major sucrose carrier PmSUC1, which was tested with detergent extracts from plasma membranes of transgenic yeast strains containing either the P. major sucrose transporter PmSUC1 or PmSUC2. The antiserum was used to determine the site of PmSUC2 expression in leaves, petioles, and roots of P. major. In cross-sections and longitudinal sections, the PmSUC2 protein was found in only one single cell type. These cells were identified as companion cells because they are nucleated, contain a dense cytoplasm, and are always adjacent to a sieve element. The labeled cells had the same longitudinal extension as did their sister sieve elements and always ended next to the sieve plates, which were characterized by specific staining. PmSUC2 mRNA and PmSUC2 protein were also detected in P. major roots. The function of PmSUC2 in the different organs and its role in phloem loading are discussed.